Association Between Plasma Redox State/Mitochondria Function and a Flu-Like Syndrome/COVID-19 in the Elderly Admitted to a Long-Term Care Unit - Grossini, Elena; Concina, Diego; Rinaldi, Carmela; Russotto, Sophia; Garhwal, Divya; Zeppegno, Patrizia; Gramaglia, Carla; Kul, Seval; Panella, Massimiliano (Frontiers in Physiology, 2021)
Background/Aims: It is widely known that the imbalance between reactive oxygen species (ROS)/antioxidants and mitochondrial function could play a pivotal role in aging and in the physiopathology of viral infections. Here, we correlated the plasma oxidants/antioxidants levels of the elderly admitted to a long-term-care (LTC) unit with clinical data in relation to flu-like disease/COVID-19. Moreover, in vitro we examined the effects of plasma on cell viability, ROS release and mitochondrial function. Materials and Methods: In 60 patients admitted to LTC unit for at least one year at moderate or high care load, demographic and clinical variables were taken. Blood samples were collected for the evaluations of oxidants/antioxidants, as thiobarbituric acid reactive substances, 8-hydroxy-2-deoxyguanosine, 8-isoprostanes, superoxide dismutase activity, glutathione and vitamin D. In vitro, human umbilical vascular endothelial cells (HUVEC) were used to examine the effects of plasma on viability, ROS release and mitochondrial membrane potential. Results: The results obtained showed that the redox state of the elderly was quite balanced; mitochondrial membrane potential of HUVEC was reduced by about 20%, only. Also, the correlation analysis evidenced the association between mitochondrial function and the patients’ outcomes. Interestingly, lower levels of mitochondrial membrane potential were found in the elderly who had symptoms suggestive of COVID-19 or with a confirmed diagnosis of COVID-19. Conclusion: The results of this study highlight the importance of mitochondrial function in the tendency to get a flu-like syndrome like COVID-19 in the elderly admitted to LTC unit. This information could have clinical implications for the management of old population.